A Study on Student Satisfaction and Continuance Intention Application Platform Based on Gamification - Chandrasari, Agnes Monica Dwi; Nugraha, Jaka (Journal of Office Administration : Education and Practice, 2023)
In this era, more and more advanced technology is available, and the technological developments that are made are very helpful to humans. The application of gamification is one of the results of technological advances, namely technological developments combined with the application of the concept of playing games into non-context games. This study aims to analyze the influence of satisfaction and continuance intention on students using gamification applications. This research is variance-based SEM with TAM and ECM models. GSCA application was used to analyze data with 83 respondents. The results of this research are that perceived usefulness has no effect on continuance intention, perceived ease of use influences satisfaction, perceived ease of use has an influence on gamification application value, gamification application value influences satisfaction, gamification application value influences continuance intention, satisfaction influences continuance intention.